Transglycosylating β‐d‐galactosidase and α‐l‐fucosidase from Paenibacillus sp. 3179 from a hot spring in East Greenland. Issue 3 (23rd December 2019) - Thøgersen, Mariane S.; Christensen, Stefan J.; Jepsen, Morten; Pedersen, Lars H.; Stougaard, Peter
Abstract: Thermal springs are excellent locations for discovery of thermostable microorganisms and enzymes. In this study, we identify a novel thermotolerant bacterial strain related to Paenibacillus dendritiformis, denoted Paenibacillus sp. 3179, which was isolated from a thermal spring in East Greenland. A functional expression library of the strain was constructed, and the library screened for β‐d ‐galactosidase and α‐l ‐fucosidase activities on chromogenic substrates. This identified two genes encoding a β‐d ‐galactosidase and an α‐l ‐fucosidase, respectively. The enzymes were recombinantly expressed, purified, and characterized using o NPG (2‐nitrophenyl‐β‐d ‐galactopyranoside) and p NP‐fucose (4‐nitrophenyl‐α‐l ‐fucopyranoside), respectively. The enzymes were shown to have optimal activity at 50°C and pH 7–8, and they were able to hydrolyze as well as transglycosylate natural carbohydrates. The transglycosylation activities were investigated using TLC and HPLC, and the β‐d ‐galactosidase was shown to produce the galactooligosaccharides (GOS) 6'‐ O ‐galactosyllactose and 3'‐ O ‐galactosyllactose using lactose as substrate, whereas the α‐l ‐fucosidase was able to transfer the fucose moiety from p NP‐fuc to lactose, thereby forming 2'‐ O ‐fucosyllactose. Since enzymes that are able to transglycosylate carbohydrates at elevated temperature are desirable in many industrial processes, including food and dairy production, we foresee the potential use of enzymes from Paenibacillus sp. 3179 in the production of, for example, instant formula. Abstract : Characterization of novel thermotolerant, transglycosylating enzymes from Paenibacillus sp., which has been isloated from a thermal spring in Greenland. The enzymes are an alpha‐fucosidase and a beta‐galactosidase, respectively. Both are able to hydrolyse as well as transglycosylate natural substrates.